A Legal Protection Of Children To Adults As Victims Parental Divorce According To The Marriage Law Number 16 Of 2019 Concerning Marriage - Hasdiana Juwita Bintang (INFOKUM, 2022)
Divorce often has a negative impact on post-divorce children. Not only disrupting growth but also disturbing the child's psychology and character. Protection in all aspects must be realized for the good of the child in the future with the guarantee of the legal rules that apply in Indonesia. The research in this writing uses normative research methods with the nature of descriptive research, while the type of data used is a literature review whose data collection materials are primary, secondary and tertiary legal materials. Legal arrangements regarding marriage in Indonesia are regulated in Law Number 16 of 2019 concerning Marriage, which explains the conditions for entering into a marriage based on the provisions stipulated in the law. Marriage is required to be notified and recorded at the Civil Registration Office. The existence of marriage will give rise to the rights and obligations of husband and wife with the aim of creating a harmonious and happy family. Divorce will occur if a husband or wife makes a mistake, namely adultery, commits domestic violence, or the husband is not willing to support and runs away from responsibilities which results in strife, bickering or debate that ends in divorce. Divorce will have an impact on the relationship between husband and wife, children and property. The importance of protecting children after a parent's divorce is something that must be guaranteed by law, both in the marriage law and the child protection law. Children as victims of parental divorce are entitled to maintenance.